2019
DOI: 10.3389/fpsyg.2019.01513
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Visual Cuing in Episodic Memory and Episodic Future Thinking in Adolescents With Autism Spectrum Disorder

Abstract: Cognitive studies generally report impaired autobiographical memory in individuals with autism spectrum disorder (ASD), but mostly using verbal paradigms. In the present study, we therefore investigated the properties of both past and future autobiographical productions using visual cues in 16 boys with ASD and 16 typically developing (TD) participants aged between 10 and 18 years. We focused on sensory properties, emotional properties, and recollection, probing past and future productions for both near and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Adolescents with ASD appear to compensate for these difficulties in AM for events by preferentially relying on their semantic knowledge. Providing visual aids or giving them more time allows them to adjust their retrieval and reconstruct a more adequate representation of memory (Bruck et al, 2007 ; Goldman, 2008 ; Crane et al, 2010 ; Bon et al, 2012 ; Brown et al, 2012 ; Terrett et al, 2013 ; Goddard et al, 2014 ; Lind et al, 2014 ; Anger et al, 2019 ). We designed our rehabilitation program accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adolescents with ASD appear to compensate for these difficulties in AM for events by preferentially relying on their semantic knowledge. Providing visual aids or giving them more time allows them to adjust their retrieval and reconstruct a more adequate representation of memory (Bruck et al, 2007 ; Goldman, 2008 ; Crane et al, 2010 ; Bon et al, 2012 ; Brown et al, 2012 ; Terrett et al, 2013 ; Goddard et al, 2014 ; Lind et al, 2014 ; Anger et al, 2019 ). We designed our rehabilitation program accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used the “From Past to Future Task” already described in a previous publication (Anger et al, 2019 ), which explores specific past personal events and future thinking for the day before (recent past), last vacation (remote past), next day (near future) and upcoming vacation (distant future). Each participant is asked to produce descriptions of memories or projections with as many details as possible, focusing on the past (i.e., one event that happened yesterday and one last summer vacation; “Can you remember something that happened to you yesterday/last summer vacation?…”
Section: Study 1: Autobiographical Memory and Social Identitymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies focusing on children and adolescents also found greater difficulties in generating scenarios happening in the future (Jackson and Atance 2008;Terrett et al 2013). Less vivid narratives (Anger et al 2019) along with difficulties in scene-construction (Ciaramelli et al 2018), self-projection (Hanson and Atance 2014;Marini et al 2016) and narrative skills (Marini et al 2019) were also reported. However, the link between EFT, AP and SF impairments has, to our knowledge, never been studied.…”
Section: Introductionmentioning
confidence: 97%